2019
DOI: 10.18568/internext.v14i3.470
|View full text |Cite
|
Sign up to set email alerts
|

Do Institutional Distances Influence South-South Cross-Border Acquisitions?

Abstract: Different countries have different institutional environments. In this way, multinational companies must deal with the difficulties imposed by the differences between their home environment and that of the country where they are inserted. In this article, we analyze the effects of institutional distance on South-South acquisitions. Specifically, we analyze the effect of institutional distance on the amount of participation chosen in Latin American international acquisitions in Brazil. More specifically, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The same results were also obtained from research (Pinto et al, 2017) which stated that companies that make cross-border acquisitions prefer full acquisitions when the institutional distance to the host country is large. This is also supported by research from (Moura et al, 2019) which stated that administrative distance has a significant and positive effect on the level of equity ownership.…”
Section: Empirical Review and Hypothesis Developmentmentioning
confidence: 53%
See 3 more Smart Citations
“…The same results were also obtained from research (Pinto et al, 2017) which stated that companies that make cross-border acquisitions prefer full acquisitions when the institutional distance to the host country is large. This is also supported by research from (Moura et al, 2019) which stated that administrative distance has a significant and positive effect on the level of equity ownership.…”
Section: Empirical Review and Hypothesis Developmentmentioning
confidence: 53%
“…Previous research (Gaffney et al, 2016) stated that economic distance affects company decisions on the level of equity ownership. This is supported by research (Moura et al, 2019;Pinto et al, 2017) which stated that economic distance affects higher equity ownership. Meanwhile, (Dikova et al, 2017;Mueller et al, 2017) found that economic distance significantly and negatively affects the level of equity ownership.…”
Section: Empirical Review and Hypothesis Developmentmentioning
confidence: 77%
See 2 more Smart Citations
“…The institutional environment strongly affects how companies perform foreign investments (Dikova & Van Witteloostuijn, 2007; Moura, Krug, Falaster, & dos Santos Parisotto, 2019). Especially, ownership choices are key decisions for companies operating CBAs and reflect how the company perceives risks and the need for control abroad (Brouthers, 2002; Chen & Hennart, 2004; Lahiri, Elango, & Kundu, 2014; Malhotra, Lin, & Farrell, 2016).…”
Section: Introductionmentioning
confidence: 99%